Implementation of the Fulfillment of Standard Operating Procedures of the Company (Turnover, Operating Hours, and Menu) at PT. Baba Rafi International - Sugara, Zona Icashya; Purwanto, Sugeng (East Asian Journal of Multidisciplinary Research, 2024)
Standard Operating Procedures (SOP) are procedures that must be followed to carry out a task or activity consistently and efficiently. SOP violations are actions that deviate from the provisions set out in a company's SOP. By using SOP, the company can achieve its goals effectively so that every company function runs properly. The method used to obtain data in carrying out research internships at PT. Baba Rafi International is a qualitative approach, where the data collection method includes direct observation in the field and documentation. The purpose of this research is to analyze the application of standard operating procedures (SOP) to employee performance. Online monitoring of operational hours is carried out with the aim of ensuring that online orders can run smoothly according to the operational hours that have been determined and if there are any negligence from the operator or problems with the application. Online menu checking is carried out to monitor the availability of raw materials to be sold online or offline. Daily turnover input is carried out twice, namely by writing paper forms manually by the operator and writing digitally with Microsoft Excel by the operational admin.